2018
DOI: 10.1111/bju.14581
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of axitinib to downstage cT2a renal tumours and allow partial nephrectomy: a phase II study

Abstract: contributed equally to this work and are equal first authors. J.-J.P. and B.E. contributed equally to this work and are equal senior authors. ObjectiveTo evaluate the ability of neoadjuvant axitinib to reduce the size of T2 renal cell carcinoma (RCC) for shifting from a radical nephrectomy (RN) to a partial nephrectomy (PN) indication, offering preservation of renal function. Patients and MethodsPatients with cT2aN0NxM0 clear-cell RCC, considered not suitable for PN, were enrolled in a prospective, multicentre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 23 publications
3
23
0
Order By: Relevance
“…Five (27.8%) patients experienced Clavien III–V post‐surgery complications. Similar to Lane et al ., the authors concluded that neoadjuvant axitinib leads to a modest decrease in tumor size that permitted downstage PN in most cases; however, procedures remained complex, requiring surgical expertise with morbidity …”
Section: Facilitating Nephron‐sparing Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Five (27.8%) patients experienced Clavien III–V post‐surgery complications. Similar to Lane et al ., the authors concluded that neoadjuvant axitinib leads to a modest decrease in tumor size that permitted downstage PN in most cases; however, procedures remained complex, requiring surgical expertise with morbidity …”
Section: Facilitating Nephron‐sparing Surgerymentioning
confidence: 99%
“…Similar to Lane et al, the authors concluded that neoadjuvant axitinib leads to a modest decrease in tumor size that permitted downstage PN in most cases; however, procedures remained complex, requiring surgical expertise with morbidity. 52 McDonald et al carried out a multicenter retrospective study to compare the renal functional outcomes of patients with complex masses who underwent neoadjuvant sunitinib therapy for imperative indications when PN was thought not to be feasible (n = 47, median tumor size 7.2 cm, median RENAL 11) with a cohort of patients with complex masses who underwent PN without prior neoadjuvant therapy (n = 78, median tumor size 6 cm, median RENAL 10). 41 The neoadjuvant treatment group received 50 mg sunitinib daily for two 6-week cycles, and the authors noted that the median tumor size and RENAL score decreased to 5.8 (P = 0.012) and 9 (P = 0.001), respectively, with 16 (34%) patients achieving PR by RECIST criteria.…”
Section: Facilitating Nephron-sparing Surgerymentioning
confidence: 99%
“…Differences in outcomes between that trial and the present one by Lebacle et al. could be explained by differences in study populations and/or drug regimens. A more recent study by Karam et al.…”
Section: Neoadjuvant Therapy To Allow Nss In Kidney Cancer: Literaturmentioning
confidence: 57%
“…In this issue of the BJU Int , Lebacle et al. evaluated the role of neoadjuvant axitinib, an oral tyrosine kinase inhibitor currently recommended as a second‐line option for metastatic clear cell RCC, to downstage cT2 kidney cancer and allow a partial nephrectomy (PN). In this multicentre prospective study, 18 patients with RCC (median tumour size 7.6 cm and R.E.N.A.L.…”
Section: Neoadjuvant Therapy To Allow Nss In Kidney Cancer: Literaturmentioning
confidence: 99%
See 1 more Smart Citation